Pengaruh Kualitas Layanan Mobile Banking Bank Bumn Terhadap Kepuasan Nasabah (Studi Pada Mahasiswa Ung Tahun 2023) - Siti Sahrina S. La Duhu; Diva Nadya Thaib; Widya Astuti Lumenta; Yayu Isyana D. Pongoliu (Peneliti.net, 2023)
This study aims to determine the influence from service quality on customer satisfaction of BUMN Bank (State-Owned Enterprises). The sample in this study were students who used mobile banking services. The data analysis technique used in this study is a test of validity and reliability, classic assumption test and multi linear regression test. While, the research method used in this research was a quantitative method. The results of this study show that the quality of service (reliability, assurance, responsiveness, tangible, and efficiency) has a positive and significant impact on banking satisfaction on mobile banking services.